2023
DOI: 10.7554/elife.86585
|View full text |Cite
|
Sign up to set email alerts
|

Continuous, long-term crawling behavior characterized by a robotic transport system

Abstract: Detailed descriptions of behavior provide critical insight into the structure and function of nervous systems. In Drosophila larvae and many other systems, short behavioral experiments have been successful in characterizing rapid responses to a range of stimuli at the population level. However, the lack of long-term continuous observation makes it difficult to dissect comprehensive behavioral dynamics of individual animals and how behavior (and therefore the nervous system) develops over time. To allow for lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…High-resolution long-term monitoring promises to expand our understanding of behavior ( Elliott et al, 2021 ). In Drosophila , continuous monitoring of larval crawling on timescales comparable with the duration of one larval instar revealed apparent epochs of faster directional movement with fewer turns followed by prolonged periods of slower movement with more turns ( Yu et al, 2023 ), a pattern strikingly similar to the one observed during long-term monitoring of C. elegans larvae ( Stern et al, 2017 ) ( Fig. 4C ).…”
Section: Resultssupporting
confidence: 58%
“…High-resolution long-term monitoring promises to expand our understanding of behavior ( Elliott et al, 2021 ). In Drosophila , continuous monitoring of larval crawling on timescales comparable with the duration of one larval instar revealed apparent epochs of faster directional movement with fewer turns followed by prolonged periods of slower movement with more turns ( Yu et al, 2023 ), a pattern strikingly similar to the one observed during long-term monitoring of C. elegans larvae ( Stern et al, 2017 ) ( Fig. 4C ).…”
Section: Resultssupporting
confidence: 58%
“…Although the adjacent bins do not show statistically significance differences, this could be a legitimate effect. Recent results (Yu et al, 2023 ) with long time scale larva thermotaxis experiments (up to 6 h) suggest two distinct groups of larvae, one group strongly navigating and the other more neutral. The neutral crawlers would be more likely to crawl in strong-cooling directions (because strong navigators turn away quickly), so perhaps they become more prevalent in the overall averaging for those conditions, leading to a reduced average turning rate.…”
Section: Resultsmentioning
confidence: 97%